Alternative Rites of Passage: Faith, rights, and performance in FGM/C abandonment campaigns in Kenya. Issue 2 (3rd April 2018) - Hughes, Lotte
ABSTRACT: Alternative Rites of Passage (ARP) are touted by NGOs and international donors as an alternative to female initiation into womanhood, but without female genital mutilation/cutting (FGM/FGC). They are becoming increasingly popular in Kenya, and with donors funding global campaigns against FGM. In these ceremonies and the instruction that precedes them, girls' human rights (mainly to life, health, education, protection) and cultural rights (manifested in teachings and ritual elements that aim to mimic the cultural traditions of the community concerned) are intertwined in one social space. ARP is discussed here in the broader context of constitutional change that has introduced the concept of cultural rights to Kenyan citizens, while simultaneously outlawing harmful cultural practices. However, the meaning of 'culture' within ARP is rarely defined by external or internal actors. Moreover, the central role of Christian faith leaders – especially Pentecostal – in ARP tends not to be regarded as cultural by local actors, including NGOs, and is largely overlooked in the scanty literature. This article argues that faith leaders' contribution to ARP constitutes significant ritualised cultural performance, but religious messages do not necessarily sit well with the more secular discourses of rights and law around FGM. ARP may be read as a newly-invented ritual that aims to replicate aspects of traditional initiation. In so doing, pick-and-mix notions of pastness, culture, social transformation and tradition are being incorporated into a hybridised ritual that its proponents present as evidence of development and modernity, and a 'harmless' alternative to FGM.